HUBUNGAN SELF-MANAGEMENT DENGAN KUALITAS HIDUP LANSIA HIPERTENSI - Gusti Nyoman Mega Utami; Desak Made Widyanthari; Ni Kadek Ayu Suarningsih (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2021)
Hypertension is a chronic disease that often occurs in elderly. Increased blood pressure in hypertension will have an impact on decreasing life quality of the elderly. Self-management plays an important role in controlling blood pressure to prevent further symptoms and complications. This study intended to define the relationship among self-management and life quality of elderly with hypertension in the working area of ??Buleleng I Public Health Center. This study was a correlative study with a cross-sectional design on 30 elderly with hypertension selected through consecutive sampling technique. The research instruments used were Hypertension Self-Management Behavior Questionnaire and Older People's Quality of Life questionnaire. The results indicated the average score of self-management and quality of life of the elderly were in good category. The results of the Spearman Rank test showed statistically there was a positive and very strong relationship among self-management and the quality of life of the elderly with hypertension in the working area of ??the Buleleng I Public Health Center (p = 0,000; r = 0,810). Elderly with hypertension were expected to improve self-management through the implementation of a healthy lifestyle and regular medical check up to the health services to improve life quality.